Statistical modelling for prediction of axis-switching in rectangular jets - Tipnis, T. J.; Knowles, Kevin; Bray, Derek (Professional Engineering Publishing, 2013)
Rectangular nozzles are increasingly used for modern military aircraft propulsion installations, including the roll nozzles on the F-35B vertical/short take-off and landing strike fighter. A peculiar phenomenon known as axis-switching is generally observed in such non-axisymmetric nozzle flows during which the jet spreads faster along the minor axis compared to the major axis. This might affect the under-wing stores and aircraft structure. A computational fluid dynamics study was performed to understand the effects of changing the upstream nozzle geometry on a rectangular free jet. A method is proposed, involving the formulation of an equation based upon a statistical model for a rectangular nozzle with an exit aspect ratio (ARe) of 4; the variables under consideration (for a constant nozzle pressure ratio (NPR)) being inlet aspect ratio (ARi) and length of the contraction section. The jet development was characterised using two parameters: location of the cross-over point (Xc) and the difference in the jet half-velocity widths along the major and minor axes (ΔB30). Based on the observed results, two statistical models were formulated for the prediction of axis-switching; the first model gives the location of the cross-over point, while the second model indicates the occurrence of axis-switching for the given configuration.